The Role of CEO Education in Moderating the Influence of Financial Performance on Stock Returns in Financial Sector Companies Listed on the Indonesia Stock Exchange in 2022-2024 - Eka Wiwid Devita; Marhaendra Kusuma; Putri Awalina (LP2M IAIN Palopo, 2026)
Stock return is one of the important indicators used to assess the success of an investment and describe the performance and prospects of a company. This study aims to analyze the effect of financial performance on stock return and also examine the extent to which CEO education can moderate this relationship among financial sector companies listed on the Indonesia Stock Exchange for the period 2022-2024. The approach used in this study is a quantitative method with panel data regression analysis techniques. Based on the Chow, Hausman, and Lagrange Multiplier tests, the most appropriate model is the Common Effect Model (CEM). Financial performance is measured using ROA, ROE, and DER, stock return is measured using the stock return formula with dividend distribution, and CEO education is measured using a dummy variable. The findings show that ROA, ROE, and DER have an effect on stock returns. In addition, CEO education does not show a significant effect in strengthening or weakening the relationship between independent and dependent variables. These results indicate that investors tend to pay more attention to information related to financial performance than to the educational background of CEOs when making investment decisions. Further research is recommended to extend the research period, increase the sample size, and include other variables that can provide a more comprehensive explanation of stock returns.